Education, educational mismatch, and wage inequality: evidence for different european countries - Santos, Marcelo Serra (2015)
In this dissertation, we study the relationship of mismatch between workers’ education and labor market requirements throughout different European countries. We found evidence in several countries that overeducated people tend to have a wage penalty and undereducated people tend to have a wage premium. This evidence contradicts the few existing evidence on the issue. However, despite the typical effects of education, tenure, experience, and gender in wages, the effects of mismatch between education and labor market requirements differ a lot throughout the wage distribution and European countries. Meanwhile, we also found a potentially new stylized fact on the relationship between returns to education and wage inequality: an inverted U-shaped relationship between returns to education and wage.